The Preparation and analysis of financial statements - Padilla, Nicanor B., Jr. ([Manila] : [GIC Enterprises & Co., Inc.], 1994)
This book was written to fill a long-felt need for a book devoted solely to financial statements and its analysis and interpretation.
CHAPTER 1. Review of accounting cycle -- 2. Balance sheet (Statement of Financial position) -- 3. Statement of income and retained earnings -- 4. Vertical and horizontal analysis -- 5. Ratio analysis -- 6. Earnings per share -- 7. Profit variation and Break-even analysis -- 8. Statement of cashflows -- 9. Accounting for changing prices -- 10. Interest : Future and present value
Keywords: FINANCIAL STATEMENTS